ANALYSIS OF STUDENTS’ LEARNING OBSTACLES ON LEARNING INVERS FUNCTION MATERIAL - Krisna Satrio Perbowo; Restu Anjarwati (Jurnal Infinity, 2017)
This research is based on the presence of obstacle in learning mathematics on inverse function. This research aims to analyze the learning obstacle, to know the types of error that is suffered by the students in learning inverse function. Kind of this kualitative research descriptive with data triangulation. The research subjects are high school students which is contained of 74 students and was taken 6 students to be main sample. The data of students’ error is obtained from the writen test result, the students’ false answers are identified into the type of error. Then it was chosen several students to be interviewed. Which the analysis result finding data in this research showed there are 4 types of errors, which are concept error, procedure error, counting error and concluding error. An obstacle which appear in learning inverse function is influenced by two factors, i.e internal factor and eksternal factor. Internal factor is showed by the students’ motivation in following learning and students’ skill in receiving learning material. While the eksternal factor is showed by the curriculum which applied in school with acceleration class caused many narrow learning time, teaching materials that is less complete with the discussion of question sample.